Relationship Between Filler-Matrix Interface and Macroscopical Properties of Polymer Nanocomposites - Aguilar Ventura, Isaac Enrique (2017)
The macroscopic properties of Multiwall Carbon Nanotube (MWCNT) polymer nano-composites and multiscale composites have been studied from a multifunctional standpoint. The objective is to understand and correlate the mechanisms in which the addition of a small content of MWCNTs can affect the mechanical, thermal and electrical properties of thermoplastic and thermoset polymer nanocomposites. While CNTs are well-known to possess extraordinary properties in the nanoscale, it has been shown that, the CNT/polymer matrix and CNT/CNT interactions are mainly responsible for the modification of properties in the nanocomposites. Observation of the mechanical properties revealed that the addition of CNTs can increase the stiffness of the material, but the increment of interfacial regions can accelerate the damage process under cyclic loading conditions. Additionally, CNTs can interact with polymer chains in the matrix affecting thermomechanical properties such as the glass transition temperature and the storage modulus. A low content of well-dispersed CNTs can form percolated networks within the matrix, which, due to the nature of the electrical conduction mechanism, have demonstrated potential in increasing the electrical conductivity of the nanocomposites. In contrast, high phonon scattering at the interconnections along the CNT network are responsible for marginal increases in thermal conductivity. In this study, a special focus was placed in modifying the CNT interconnections with a conductive polymer "bridge" to increase the efficiency of the electrical carrier transport. Additional experimental observations such as piezoresistivity and electrical conductivity/temperature dependency, demonstrated the major role of the interfacial regions with respect to the observed material properties in the macroscale. Controlling the interactions that occur in these regions is key to achieve tailorable, multifunctional nanocomposites.